Unraveling the Role of Oxygen Pulse Variability in Endurance Exercise Training in Individuals with COPD: A Novel Approach to Response of Oxygen Pulse and Quality of Life in Pulmonary Rehabilitation - Huang SY; Hsieh PC; Huang KL; Yang MC; Jao LY; Tzeng IS; Lan CC; Wu YK (International Journal of COPD)
Shiang-Yu Huang,1 Po-Chun Hsieh,2 Kuo-Liang Huang,3,4 Mei-Chen Yang,3,4 Lun-Yu Jao,3,4 I-Shiang Tzeng,5 Chou-Chin Lan,3,4,* Yao-Kuang Wu3,4,* 1Division of Respiratory Therapy, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, New Taipei City, Taiwan, Republic of China; 2Department of Chinese Medicine, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation; School of Post-Baccalaureate Chinese Medicine, Tzu Chi University, Hualien, Taiwan, Republic of China; 3Division of Pulmonary Medicine, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, New Taipei City, Taiwan, Republic of China; 4School of Medicine, Tzu-Chi University, Hualien, Taiwan; 5Department of Research, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, New Taipei City, Taiwan, Republic of China*These authors contributed equally to this workCorrespondence: Yao-Kuang Wu, Division of Pulmonary Medicine, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, 289, Jianguo Road, Xindian City, New Taipei City, 23142, Taiwan, Republic of China, Tel +886-2-6628-9779 ext. 2259, Fax +886-2-6628-9009, Email drbfci@yahoo.com.twBackground: Chronic obstructive pulmonary disease (COPD) is characterized by airway inflammation, airflow limitation, reduced health-related quality of life (HRQL), and exercise intolerance. Pulmonary rehabilitation (PR) is essential for COPD management, but outcomes may be influenced by individual physiological factors. Cardiopulmonary exercise testing (CPET) measures oxygen pulse (O2P), an indicator of stroke volume, yet the impact of baseline O2P on PR effectiveness remains unclear.Methods: This retrospective study included 97 participants with COPD who had received PR, of whom 48 were classified as Group 1 (normal O2P) and 49 as Group 2 (low O2P). PR involved 12 weeks of hospital-based endurance training on a bike, performed twice a week. Participants were assessed before and after PR using spirometry, respiratory muscle strength measurements, CPET, and HRQL evaluation with the St. George’s Respiratory Questionnaire (SGRQ).Results: PR significantly improved exercise capacity (peak work rate and oxygen consumption), dyspnea score, and all domains of the SGRQ, maximum expiratory pressure, ventilatory equivalent, respiratory rate, and mean blood pressure at rest in both groups (p < 0.05). However, improvements in O2P, maximal inspiratory pressure, and tidal volume at rest were observed only in Group 2 but not in Group 1.Conclusion: PR improves exercise capacity, HRQL and specific respiratory function in participants with COPD, regardless of baseline O2P levels. Individuals with lower baseline O2P experience more benefits from PR, including a significant increase in O2P.Keywords: Chronic obstructive pulmonary disease, COPD, Oxygen pulse, Pulmonary rehabilitation